Brazilian clays for environmental solutions applied to radioactive waste management (Brazilian Journal of Radiation Sciences, 2021)
Clays have been adopted in most nuclear waste producing countries as a key constituent in engineered barrier systems for final disposal facilities at all levels of radioactive wastes (LILW-SL, LILW-LL, and HLW). The following study presents a thorough characterization upon five Brazilian clay-rich deposits, mostly smectite bearing clays, aiming to evaluate their expected performance as barrier under the conditions associated to a Low and Intermediate Level Waste Repository; being the former a matter of national strategic interest. Samples coming from the Brazilian states of Paraná, Bahia, Paraíba, and Maranhão were treated and analyzed by means of X-Ray diffraction as main technique, and complemented by FTIR, LALLS, XRF, and SEM-EDS, in order to establish the mineralogical composition, particle size distribution, and chemical composition. Moreover, several standard clay treatments over the